(untitled) (Journal of Science and Technology, 2016)
A study was carried out in the Upper East Region of Ghana to assess the on-site effects and the cost of fertility erosion from five small reservoir catchments (Dua, Doba, Zebilla, Kumpalgogo and Bugri). The catchment soils and reservoir sediments were sampled and analyzed for their bulk density and nutrient content. The mean reduction in soil depth in the various catchments was 3.996±3.806 mm y-1 in the order of Kumpalgogo>Dua>Bugri>Zebilla>Doba. The corresponding decrease in the water holding capacity of the top 20 cm depth of the catchment soils ranged from 0.563 to 4.698 % per year. The percentage loss in the total nutrient stocks in the top 20 cm of the catchments as eroded sediment-bound nutrients ranged from 9.63 to 64.71, 7.87 to 56.83, 6.12 to 54.82, 1.26 to 40.14, 49.86 to 12.65, 16.84 to 72.07 for OC, N, P, K, Ca and Mg, respectively. The total amount of nutrient loss in kg ha-1 among the reservoirs ranged from 2383 to 19672 for OC, 153 to 3048 for N, 3.15 to 42.59 for P, 41 to 290 for K, 432 to 2158 for Ca, and 63 to 483 for Mg. The cost of N, P and K removed by erosion was calculated by the Replacement Cost Method. The total cost per year (GH¢ ha-1 y-1) of fertilizers (sulphate of ammonia, single superphosphate and muriate of potash) was 286.15 for Dua, 74.289 for Doba, 225.061 for Zebilla, 1119.997 for Kumpalgogo and 96.376 for Bugri. The study has amply shown that soil loss through erosion reduces top soil depth, nutrient stocks and the water holding capacity of catchment soils. This will adversely affect crop productivity if no control measures are implemented. This can also lead to land degradation.